1995
DOI: 10.1111/j.1651-2227.1995.tb13547.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic active Epstein‐Barr virus infection in children in Japan

Abstract: The patients with chronic active Epstein-Barr virus infection (CAEBV) in childhood in Japan are described. Among 39 registered cases, 20 patients were males and 19 were females. Unlike the X-linked lymphoproliferative syndrome, there was no hereditary background. The incidence of hypersensitivity to mosquito bites was high (31.3%) as a past history. Most patients exhibited hepatomegaly (92.3%), splenomegaly (87.2%) and fever (84.6%). The incidence of absent anti-EB virus nuclear antigen titres was unexpectedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
76
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 19 publications
2
76
0
Order By: Relevance
“…The following clinical features are commonly noted in patients with CAEBV [19][20][21]. Symptoms are persistent and chronic and generally consist of prolonged or intermittent fever, lymphadenopathy, and/or hepatosplenomegaly.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The following clinical features are commonly noted in patients with CAEBV [19][20][21]. Symptoms are persistent and chronic and generally consist of prolonged or intermittent fever, lymphadenopathy, and/or hepatosplenomegaly.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Caution should be exercised in diagnosing CAEBV initially in the presence of these diseases. Skin lesions such as hypersensitivity to mosquito bites were characteristic in some patients with CAEBV who may suffer from the granular lymphocyte proliferative disorder or clonal T-cell lymphoproliferation [21,[24][25][26], and various cutaneous manifestations, including hydroa vacciniforme-like eruptions, were recently reported to be associated with T-cell or NK-cell LPDs having chronic activated EBV infections [27].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…13 It was reported that NK cell leukemia/lymphoma occasionally occurred after CAEBV infection and the prognosis was very poor. 3,4 Here we describe a first such patient, who was successfully treated with allogeneic bone marrow transplantation (BMT) from an HLA-identical sibling donor.…”
mentioning
confidence: 99%
“…3,4 An effective treatment has yet to be established partly because CAEBV infection is rare. 3 Recently, allogeneic blood stem cell transplantation was reported to be effective in eradicating EBV-infected cells. 5,6 Kuzushima et al 7 described that an adoptive transfer of anti-EBV cytotoxic T lymphocytes (CTLs) from an HLA-matched sibling to a patient with severe CAEBV infection transiently reduced the amount of EBV DNA, but was not able to completely eradicate the EBV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation